Temporal and spatial arrangement of wheat sowing date: a revolutionary strategy to accomplish Tianfu Granary - Tan, Feiquan; Hou, Yulian; Huang, Xinyu; Jia, Jia; Yang, Huai; Luo, Peigao (Frontiers in Plant Science, 2023)
Abstract： Rapidly global urbanization and economic growth in the past several decades have resulted in a sharp contraction of arable areas worldwide. However, food supply requirements are quickly increasing due to higher living standards and larger populations. Therefore, food crises are still a major threat to human society. The conflict between farmland areas and the increasing need for essential supplies is becoming acuter in China. Therefore, we suggest that a novel strategy would address the issue, in which temporal and spatial arrangement of wheat sowing dates would be highly focused.